Radiofrequency Ablation vs. Surgical Resection for Small Early-Stage Primary Intrahepatic Cholangiocarcinoma - Xiang, Xin; Hu, Daixing; Jin, Zheng; Liu, Pan; Lin, Huapeng (Frontiers in Oncology, 2020)
Aim: We aimed to compare the survival outcomes of radiofrequency ablation (RFA) and surgical resection (SR) for patients with small early-stage primary intrahepatic cholangiocarcinoma (ICC). Methods: Patients with small (≤5 cm) and early-stage ICC were screened from the Surveillance, Epidemiology, and End Results (SEER) database. Overall survival (OS) and cancer-specific survival (CSS) rates between the SR and RFA patients were evaluated. The results were verified using an inverse probability-weighting model (IPTW). Results: In total, 184 patients with small T1 stage ICC that received RFA or SR treatment were identified. The OS rates at 1, 3 and 5 years were 87.4%, 73.3% and 61.5% for patients underwent SR, respectively, and 89.9%, 42.4% and 23.9%, respectively, for patients received RFA. CSS rates at 1, 3 and 5 years were 91.5%, 73.8% and 66.1%, respectively, for the SR group and 93.5%, 53.4% and 30.0%, respectively, for the RFA group. The OS and CSS rates were evaluated to be significantly better in the SR group than in the RFA group after the multivariate Cox regression and IPTW analysis. Subsequently, the survival benefit of SR were also observed in the subgroup of patients with ＜4.5cm or ＜4cm early stage ICC when compared with RFA. Conclusion: Our results indicated that the SR provided a significantly better prognosis than RFA in patients with small and early stage ICC. SR as the first-line treatment of primary early-stage ICC is still recommended. However, prospective randomized controlled trials with larger sample sizes are required to compare these modalities in the treatment of ICC.